Combination Method of Singing and Storytelling to Improve Knowledge of Dental and Oral Health Maintenance in Elementary School Students - Hasan, Annida Aulia; Nurdiansyah, Novia Febrianti (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: Indonesian people have 57.6% dental and oral health problems. Ignorance of dental and oral hygiene is a behavioral element that contributes to dental and oral health problems in the population. This comes from a lack of understanding of dental hygiene and care. One of the most effective ways to instill habits in children in maintaining dental and oral health is through dental and oral health education or counseling efforts, one of which is through singing and storytelling methods. Objective: To analyze the effectiveness of knowledge of dental and oral health maintenance before and after education with a combination of singing and storytelling methods in elementary school students. Method: This study used a quasi-experimental design with a one-group pretest-posttest design. The instrument used was a questionnaire sheet and data analysis using the Wilcoxon test. Results: The results of this study indicate that the average knowledge before counseling was 5, while after counseling it was 9.3, with p = 0.000 (p <0.05). Conclusion: The combination of singing and storytelling methods is effective in increasing knowledge of dental and oral health maintenance